Costs of Climate Information Services Development and Implementation - List, Geneva; Kramer, Berber; Timu, Anne G.; Zebiak, Stephen E.; Rose, Alison (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) works to facilitate and scale the development of tailored CIS and climate-smart agriculture making it accessible to smallholder farmers in six target countries. However, the costs and benefits of providing CIS to smallholder farmers have not yet been well-documented. AICCRA is developing a methodology and toolkit to help stakeholders assess the public and private costs and benefits of CIS to provide economic justification for these interventions. This in turn is expected to improve investments in adaptation and ensure that limited resources are being spent effectively.